Information overload : a system for better managing everyday data - Pijpers, Guus, 1960- (Hoboken, N.J. : Wiley ; Chichester : John Wiley [distributor], 2010)
Examining the characteristics of information and the latest findings in cognitive science, this book shows how the mind works, how it can be used to think optimally about your business, and how to improve business performance with better information management practices.
Formerly CIP.
Includes bibliographical references (p. 185-190) and index.
Keywords: Knowledge management; Information behavior